USERfit - Design for all methods and tools - Colette Nicolle (1999)
What can we do as ergonomists to promote design for all (or at least design solutions that will include a greater number of people)? Perhaps the best answer we can offer comes from Rudyard Kipling: I have six honest serving men, they taught me all I knew. Their names are ‘What’, ‘Why’, ‘When;, ‘Where’, ‘How’ and ‘Who’ (Rudyard Kipling, The Just So Stories)